PENGARUH METODE BERCERITA KISAH SAHABAT RASUL TERHADAP PENINGKATAN NILAI MORAL ANAK USIA DINI DI RAUDHATUL ATHFAL AL MIZAN - Nor Amalia Abdiah (Institut Agama Islam Darul Ulum Kandangan, 2022)
Islam teaches about moral values, one of which is through God's chosen persons set out in history. This paper describes the method of telling the story of prophet`s companions as the delivery of a message of moral value in the comprehension of a story connected with the daily life of early childhood. The method used in this research is pre-experimental and post-test, data analysis used is the Wilcoxon Signed Rank Test z Score. This pre-experimental process found that not all R A teachers were able to tell the story of the Prophet's companions. Increasing the moral value of early childhood is influenced by the teacher's story telling method, especially about the story of the companions of the Prophet. The findings obtained from the results of this study The following is the added value of early childhood issued by the method taken by the teacher about the story of the companions of the Prophet, namely by comparing the results of the average score before and being prepared, namely the pre-test results of 155,7333 and post test of 190,22667. The statistical results of the hypothesis test using the Wilcoxon Signed Rank Test Z obtained by -3,300> z table -1,645 with a P value (Asymp.Sig.2 tailed) of 0.001 which is smaller than the limitation of the study / level of research results <0.05, which means there is a significant improvement from the method of telling the story of the Companions of the Prophet to the increase in early childhood moral values ??in RA Al Mizan